GnRHa/Stanozolol Combined Therapy Maintains Normal Bone Growth in Central Precocious Puberty - Zhu, Shunye; Long, Lingli; Hu, Yue; Tuo, Ying; Li, Yubin; Yu, Zhenhua (Frontiers in Endocrinology, 2021)
Background Gonadotropin-releasing hormone agonist (GnRHa) is the gold standard in the treatment of Central Precocious Puberty (CPP) with progressive puberty and accelerative growth. However, GnRHa treatment is reported to result in growth deceleration and prevents growth plate development which leads to a reduction in height velocity. Stanozolol (ST) has been used to stimulate growth in patients with delayed growth and puberty, nevertheless, the effects and mechanisms of ST on CPP with GnRHa treatment are currently unclear. Methods and Results In the current study, we recorded the following vital observations that provided insights into ST induced chondrogenic differentiation and the maintenance of normal growth plate development: (1) ST efficiently prevented growth deceleration and maintained normal growth plate development in rats undergoing GnRHa treatment; (2) ST suppressed the inhibitory effect of GnRHa to promote chondrogenic differentiation; (3) ST induced chondrogenic differentiation through the activation of the JNK/c-Jun/Sox9 signaling pathway; (4) ST promoted chondrogenic differentiation and growth plate development through the JNK/Sox9 signaling pathway in vivo. Conclusions ST mitigated the inhibitory effects of GnRHa and promoted growth plate development in rats. ST induced the differentiation of chondrocytes and maintained normal growth plate development through the activation of JNK/c-Jun/Sox9 signaling. These novel findings indicated that ST could be a potential agent for maintaining normal bone growth in cases of CPP undergoing GnRHa treatment.